Highly active antiretroviral therapy interruption: predictors and virological and immunologic consequences. - Touloumi, G; Pantazis, N; Antoniou, A; Stirnadel, H; Walker, SA; Porter, K (2006)
OBJECTIVE: To characterize the magnitude and the predictors of highly active antiretroviral therapy (HAART) interruption (TI) and to investigate its immunologic and virological consequences. METHODS: Using Concerted Action on Seroconversion to AIDS and Death in Europe data from 8,300 persons with well-documented seroconversion dates, we identified subjects with stable first HAART (for at least 90 days) not initiated during primary infection. A TI was defined as an interruption of all antiretroviral therapy drugs for at least 14 days. RESULTS: Of 1,551 subjects starting HAART, 299 (19.3%) interrupted treatment. Median (interquartile range) duration of the TI was 189 (101-382) days. The cumulative probability (95% confidence interval) of TI at 2 years was 15.9% (14.0%-18.1%). Women were more likely to have a TI than men in the same exposure group (35.8% vs 24.2% among drug users, 22.1% vs 13.3% among heterosexuals; P < 0.05). Higher baseline viremia and poor immunologic response to HAART were associated with higher probabilities of TI. Median (interquartile range) individual CD4 cell loss during TI was 94 (1-220) cells/microL. Older age at HAART (>40 yr), lower pre-HAART nadir (<200 cells/microL), and lower CD4 at start of TI (<350 cells/microL) were significantly associated with greater relative CD4 loss during TI. CONCLUSIONS: We estimate that almost 1 in 6 subjects on HAART interrupts treatment by 2 years. Further research is needed to investigate the reasons why TI is higher in women. We have identified characteristics of subjects with the greatest risk for CD4 loss in whom TI may have greater risks.